2020
DOI: 10.1016/j.chempr.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecules in Confined Spaces: Reactivities and Possibilities in Cavitands

Abstract: Template effects are at the origin of supramolecular chemistry, but the behavior of folded molecules is a relatively new undertaking. Water-soluble cavitand hosts bind hydrocarbons through hydrophobic effects and force long-chain guests into folded conformations. This brings their ends closer together, and sites that were remote in solution become neighbors in the confined space and affect each other's reactivity. Amphiphilic guests fold in the cavitand to bury hydrophobic surfaces and expose the hydrophilic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 87 publications
(43 reference statements)
2
57
0
Order By: Relevance
“…1,[8][9][10][11] A large variety of molecular hosts bearing functional nanocavities has been reported to date, including cyclodextrins, carcerands, cavitands, calixarenes, cryptophanes, and cucurbiturils. 12 Moreover, several host-guest systems have shown the ability to tune photo-optical properties of their guest molecules and facilitate their solubilisation. 13,14 In this regard, programmed self-assembly became a key facilitator in the fabrication of innovative compartmentalized nanostructures, making use of non-covalent interactions among distinct molecular building blocks, 15,16 and/or exploiting specific templates or stimuli to modulate their selfassembly process.…”
Section: Introductionmentioning
confidence: 99%
“…1,[8][9][10][11] A large variety of molecular hosts bearing functional nanocavities has been reported to date, including cyclodextrins, carcerands, cavitands, calixarenes, cryptophanes, and cucurbiturils. 12 Moreover, several host-guest systems have shown the ability to tune photo-optical properties of their guest molecules and facilitate their solubilisation. 13,14 In this regard, programmed self-assembly became a key facilitator in the fabrication of innovative compartmentalized nanostructures, making use of non-covalent interactions among distinct molecular building blocks, 15,16 and/or exploiting specific templates or stimuli to modulate their selfassembly process.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It follows that it is of interest to develop strategies for building superstructures of greater complexity and diversity than is presently the norm. [6][7][8][9] While scaffolded multi-walled polyhedra [10][11][12][13][14] and Russian doll complexes [15][16][17][18][19][20][21][22] have been constructed using metal coordination, 10,12,14,19,[23][24][25][26] DNA origami, 11,27,28 and host-guest complexation, [16][17][18]20,21,29,30 closed-surface multi-walled superstructures are extremely rare 4 because of the need to design outer and inner building blocks that complement each other geometrically and stereoelectronically.…”
Section: Introductionmentioning
confidence: 99%
“…The most plausible possibilities within the pillar[5]arene cavity are the pseudo‐rotaxane‐like structures shown in Figure 4 a and Figure 4 b; structures like those shown in Figures 4 c and 4d are more likely to occur in concave systems. [ 66 , 67 , 68 , 69 ]…”
mentioning
confidence: 99%
“…The most plausible possibilities within the pillar [5]arene cavity are the pseudo-rotaxane-like structures shown in Figure 4a and Figure 4b; structures like those shown in Figures 4c and 4d are more likely to occur in concave systems. [66][67][68][69] In complexes with compound 1, the alkyl chain of 1,ω-disubstituted alkanes may, in principle, adopt an extended, bended, or even coiled form. For example, we found that the short adiponitrile guest (6 a) forms a pseudo-rotaxane-like type complex with 1 as shown in Figure 4a.…”
mentioning
confidence: 99%